From Cards to Creatures: Interactive 3D Generation Using GenAI - Johnson, Edward Scott Carvalho; Dangoni, Arthur Galdino; Borges, Pedro Elias Engelberg Silva; Silva, Diogo Fernandes Costa; Galvão Filho, Arlindo Rodrigues (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
We present “From Cards to Creatures”, a mobile augmented reality system that enables interactive 3D visualization of physical trading cards through generative AI. The proposed pipeline combines object detection, retrieval, and image-to-3D generation to support real-time rendering anchored to physical inputs. Specifically, a YOLOv11-based detector identifies and extracts the card’s unique ID from the mobile camera feed, which allows for instant retrieval of the corresponding 3D asset from a pre-compiled dataset. Each card’s artwork is processed with the Hunyuan3D-2.1 generative model to produce high-quality meshes and textures. The retrieved model is rendered and spatially aligned with the detected card in the AR scene. By decoupling the generation process from real-time image capture, the system ensures consistent reconstruction and low-latency inference. A qualitative evaluation using collectible Pokémon cards demonstrates accurate alignment, coherent shape generation, and responsiveness during interaction. This case study illustrates a modular architecture that can be extended to other domains involving physical artifacts and generative 3D content.